Research Priorities in Pediatric Palliative Care - Baker, Justin N. (J Pediatr, 2015)
OBJECTIVE: To synthesize the perspectives of a broad range of pediatric palliative care (PPC) clinicians and parents to formulate a consensus on the prioritization of the PPC research agenda. STUDY DESIGN: A 4-round modified Delphi online survey was administered, to PPC experts and to parents of children who had received PPC. In Round 1, research priorities were spontaneously generated. Rounds 2 and 3 then served as convergence rounds to synthesize priorities. A fourth iteration asked participants to rank the research priorities that had reached at least 80% consensus. RESULTS: A total of 3093 concepts were spontaneously generated by 170 experts and 72 parents in Round 1 (65.8% response rate [RR]). These concepts were thematically organized into 78 priorities and recirculated for Round 2 ratings (n = 130, 53.7% RR). Round 3 achieved response stability, with 31 consensus priorities oscillating within 10% of the mode (n = 98, 75.4% RR). Round 4 resulted in consensus recognition of 20 research priorities, which were thematically grouped as decision making, care coordination, symptom management, quality improvement, and education. CONCLUSIONS: This modified Delphi survey used professional and parental consensus to identify preeminent PPC research priorities. Attentiveness to these priorities may help direct resources and efforts toward building a formative evidence base. Investigating PPC implementation approaches and outcomes can help improve the quality of care services for children and families.